Feminist Analysis of Brit Bennett’s “The Vanishing Half” - Ratna Sari Dewi; Rahmah Fithriani; Pardi Pardi (LPPM Universitas Bumigora Mataram, 2026)
This research aims to explore how women’s experiences and gender inequality are depicted in Brit Bennett’s novel The Vanishing Half, using a feminist literary-critical approach. The story of this novel follows the lives of two twin sisters, Desiree and Stella Vignes, whose choices about their identity and social position reflect issues such as race, class, and gender-based oppression in 20th-century America. This study employs descriptive qualitative methods and draws on feminist theory, particularly liberal feminism and intersectional approaches, to analyze how female characters in the novel struggle against patriarchal domination and racial hierarchy. The results of the study show that Bennett’s work expresses feminist ideals, as her female characters reject conventional female roles and affirm their ability to determine their own destinies despite facing obstacles from the existing system. Furthermore, this research also provides insight into the novel’s depiction of the double oppression experienced by Black American women, influenced by race and gender. The Vanishing Half explores the role of women and highlights identities that are entwined by multiple factors. This study concludes that the feminist perspective provides a deeper insight into how women’s voices are shaped, suppressed, and finally empowered in a race-based social system.